2008
DOI: 10.1007/s00441-008-0696-3
|View full text |Cite
|
Sign up to set email alerts
|

Fetal mesenchymal stem cells derived from human umbilical cord sustain primitive characteristics during extensive expansion

Abstract: Stem cells of fetal origin lie between embryonic and adult stem cells in terms of potentiality. Because of the ethical controversy surrounding embryonic stem cells and the relatively inferior quality of adult stem cells, the use of fetal stem cells would be an attractive option in future therapeutic applications. Here, we have investigated primitive characteristics of human umbilical-cord-derived fetal mesenchymal stem cells (UC fMSCs) during extensive expansion. We have successfully isolated and cultured UC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 39 publications
2
81
0
Order By: Relevance
“…Go et al (18) reported that MSCs lost their stem cell characteristics after several generations but would maintain the potential for the proliferation and differentiation through transduction Sox2 or Nanog gene into the MSCs. And the levels of OCT4, Nanog, Sox2, and TERT mRNA expression correlated positively with the undifferentiated state, suggesting that OCT4, Nanog, Sox2, and TERT mRNA could be used as a sign of undifferentiated MSCs (18,19). Greco et al (12) found that these embryonic transcription factors could also be indicators of MSCs differentiation potential as an experimental tool and also in clinical diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…Go et al (18) reported that MSCs lost their stem cell characteristics after several generations but would maintain the potential for the proliferation and differentiation through transduction Sox2 or Nanog gene into the MSCs. And the levels of OCT4, Nanog, Sox2, and TERT mRNA expression correlated positively with the undifferentiated state, suggesting that OCT4, Nanog, Sox2, and TERT mRNA could be used as a sign of undifferentiated MSCs (18,19). Greco et al (12) found that these embryonic transcription factors could also be indicators of MSCs differentiation potential as an experimental tool and also in clinical diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…However, in certain degenerative diseases, such as osteoarthritis, MSCs are depleted and have reduced ability to differentiate and proliferate [6] . As an alternative source of MSCs, young cells such as fetal (f) MSCs could be harvested from the umbilical cord, placental stroma, and the amnion [7][8][9] . Ethical concerns regarding the isolation of MSCs from fetal sources are minimized, as these tissues are normally discarded after birth [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Jo et al, [76] have shown that pluripotent stem cell markers, such as Oct-4, SSEA-3, SSEA-4, Tra-1-60, and Tra-1-81, are expressed, as both mRNA and protein, by MSCs from the whole cord and their expression levels are maintained up to the 9 th passage. Furthermore, Qiao et al, [75] have detected nucleostemin, a p52 binding protein localized in nucleoli of stem cells [82], and BMI-1 involved in self-renewal [83], whereas La Rocca et al, [77] have demonstrated, for the first time, the presence of both isoforms of Oct-4 (A and B).…”
Section: Mscs From Whole Umbilical Cordmentioning
confidence: 99%
“…Also in this case, the incubation times greatly differ from one laboratory to another, ranging from 10 min to 3 h. The most frequently used culture medium is DMEM-LG supplemented with 10% FBS or FCS. However, growth factors, such as vascular endothelial growth factor (VEGF), EGF, and bFGF, have been also added [72,76,79]. A comparison between the explant method and enzymatic digestion was carried out by Schugar et al, [81], which demonstrated that the isolation method affects population phenotype.…”
Section: Mscs From Whole Umbilical Cordmentioning
confidence: 99%
See 1 more Smart Citation